DESIGN OF ELECTRONIC MEDICAL RECORD INFORMATION SYSTEM AT UNIVERSITY OF INDONESIA STUDENT HEALTH CENTER (PKM UI) - Astina Atikah Sultan (Jurnal EduHealth, 2020)
This thesis discusses the design of the medical record information system at the University of Indonesia Student Health Center (PKM UI). The purpose of this thesis is to design an electronic medical record information system in PKM UI that is useful to produce valid, complete, and timely information and to support the improvement of patient services in PKM UI. This research uses qualitative methods. And system design is done using the system development life cycle (SDLC)stages. The results of this study are in the form of the design of electronic medical record information systems in PKM UI.